2016
DOI: 10.1634/theoncologist.2015-0248
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and Phosphatidylinositol 3-Kinase/Protein Kinase B/Mammalian Target of Rapamycin (PI3K/AKT/mTOR) Inhibitors in Phase I Trials: Incidence, Predictive Factors, and Management

Abstract: Background. Dysregulation of the phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway is implicated in human cancer growth and progression. Agents targeting this pathway are associated with hyperglycemia due to interaction with the insulin-glucose regulatory axis. Identifying the predictive factors for hyperglycemia in patients treated with these agents may help direct future management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…We find that high insulin treatment triggered insulin resistant by the overexpression of IRS and mTOR, and galangin treatment downregulated IRS and mTOR phosphorylation ( Figure 4(a) ). This result is consistent with the conclusions that the activity of mTOR can be inhibited by downregulating the serine phosphorylation of IRS and upregulating its tyrosine phosphorylation [ 38 ]. Activated mTOR phosphorylates p70S6K, one of the most studied substrates of mTOR.…”
Section: Discussionsupporting
confidence: 92%
“…We find that high insulin treatment triggered insulin resistant by the overexpression of IRS and mTOR, and galangin treatment downregulated IRS and mTOR phosphorylation ( Figure 4(a) ). This result is consistent with the conclusions that the activity of mTOR can be inhibited by downregulating the serine phosphorylation of IRS and upregulating its tyrosine phosphorylation [ 38 ]. Activated mTOR phosphorylates p70S6K, one of the most studied substrates of mTOR.…”
Section: Discussionsupporting
confidence: 92%
“…Rapamycin has been reported to cause certain clinicopathologic changes when given to human patients at immunosuppressive doses (Brattstrom et al 1998;Khan et al 2016;Alexandre et al 1999), but this study provides the first comparable data for dogs given rapamycin in non-immunosuppressive doses. While the pharmacokinetics and pharmacodynamics of both orally and parenterally administered rapamycin in dogs are known (Paoloni et al 2010;Larson et al 2016), no data on its use for periods exceeding 7 days in companion dogs have been previously published.…”
Section: Side Effectsmentioning
confidence: 78%
“…Rapamycin is also used clinically for some rare forms of cancer (Xie et al 2016), to treat tuberous sclerosis complex, and in cardiac stents, to prevent restenosis (Kaeberlein 2013). Several side effects have been associated with rapamycin and rapamycin derivatives at the doses used in human medicine, including stomatitis (Boers-Doets et al 2013), impaired wound healing (Weinreich et al 2011), hyperlipidemia (Brattstrom et al 1998), hyperglycemia (Khan et al 2016), and thrombocytopenia (Alexandre et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…mTOR is a major node in the pathway; approximately 50% of solid tumours are associated with the activation of the PI3K–Akt–mTOR pathway ( Liu P. et al, 2009 ). Khan et al (2016) found that hyperglycaemia is common in patients treated with PI3K–Akt–mTOR inhibitors; the agents targeting this pathway are associated with hyperglycaemia due to their interaction with the insulin–glucose regulatory axis. Recently, it was reported that NLRC3 is an inhibitory sensor of the PI3K–mTOR pathway in cancer ( Karki et al, 2016 ); however, the relationship between NLRC3 and PI3K–Akt–AS160–GLUT4, NLRC3 and PI3K–Akt–mTOR signalling pathway in DM is not known.…”
Section: Discussionmentioning
confidence: 99%